2000
DOI: 10.1207/s15327647jcd0104_02
|View full text |Cite
|
Sign up to set email alerts
|

Advancing Downward to the Basic Level

Abstract: In 3 experiments, we studied whether infants and young children understand various basic-level conceptual distinctions in the domains of household artifacts, animals, and vehicles. Using small replicas, we modeled events such as washing dishes in a sink for children 14, 19, and 24 months old, and then gave them an exemplar from the same basic-level concept (another sink) and an exemplar of another concept from the same domain (bathtub). We measured which object they used to imitate the event. Fourteen-month-ol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 31 publications
3
24
0
Order By: Relevance
“…Thus, our findings from the object examination task, the sequential touching task, and the generalized imitation task converge on the conclusion that infants initially form broad, relatively undifferentiated concepts of animals, vehicles, furniture, and plants (with some evidence that artifacts become differentiated earlier than animals and plants, including earlier correct assignment of basic-level properties; Mandler & McDonough, 1999). Furthermore, these tasks all indicate that these domain-level concepts are not organized around individual features or overall perceptual appearance, but rather around some (possibly quite primitive) notion of kind.…”
Section: Conceptual Categories Are Used For the First Inductive Infersupporting
confidence: 64%
See 1 more Smart Citation
“…Thus, our findings from the object examination task, the sequential touching task, and the generalized imitation task converge on the conclusion that infants initially form broad, relatively undifferentiated concepts of animals, vehicles, furniture, and plants (with some evidence that artifacts become differentiated earlier than animals and plants, including earlier correct assignment of basic-level properties; Mandler & McDonough, 1999). Furthermore, these tasks all indicate that these domain-level concepts are not organized around individual features or overall perceptual appearance, but rather around some (possibly quite primitive) notion of kind.…”
Section: Conceptual Categories Are Used For the First Inductive Infersupporting
confidence: 64%
“…They have begun to narrow the artifact characteristics appropriately, but are still overgeneralizing the natural kind characteristics (presumably because of fewer interactions with animals and plants than with artifacts). We have since replicated these findings with other properties and shown that the overgeneralizations made do not extend beyond domain boundaries; for example, 14-month-olds use a toothbrush to groom hair but not a spoon, and they hammer with a wrench but not a cup (Mandler & McDonough, 1999). Needless to say, we do not conclude that young children cannot restrict inductions to subcategories in either natural kind or artifact domains.…”
Section: Conceptual Categories Are Used For the First Inductive Infermentioning
confidence: 56%
“…Whereas some researchers find categorization primarily limited to the global level (e.g., Mandler & McDonough, 2000), others find more extensive categorization at global, basic, and subordinate levels (e.g., Quinn, 2002). Among numerous methodological differences between the studies at issue, one key difference is that Mandler and McDonough used toy objects as stimuli, and Quinn and colleagues used photographs.…”
Section: Discussionmentioning
confidence: 99%
“…So if a dog is shown being given a drink or being put to bed, when infants are given various animal models to use to imitate the events they have seen, they pick any mammal randomly, hence being as likely to use a cat or a rabbit to imitate the event as another dog (Mandler & McDonough, 1998a). Differentiation into finer conceptual categories occurs gradually over the course of the second year (Mandler & McDonough, 2000) and beyond (Bornstein & Arterberry, 2010; Mandler, Bauer, & McDonough, 1991).…”
Section: The First Object and Relational Concepts Are Based On Attmentioning
confidence: 99%